Accurate Analysis of Double Ten Bar Mechanism Linked by one joint - Salem, Salem Nazih; Hasan, Mustafa Rafik (Journal of natural sciences, life and applied sciences, 2019)
Most of companies wish to decrease maintenance and on the other hand having the same target with low weight and no friction although it may cost more, when a machine is built. Using flexural (also flexure) hinges in a system, at least, leads to all of these advantages. Considering a planar mechanical system consists of double ten bar mechanism with revolute joints, we replace each revolute joint with super elastic hinge. Doing so, we have a gate to build a system, strongly recommended, to achieve the same goal using minimum energy. The main purpose of this paper is to elaborate a mathematical apparatus able to estimate the deviations of the considered system before and after replacing revolute joints taking into account the real performance of the novel system through large bending displacements in the flexure (flexural) hinges.